The Protective Effects of Ramadan Fasting against Cancer: Exploring Metabolic, Cellular, and Epigenetic Mechanisms - Jonas, Ajibu; Hassan, Charles; Saidi, Yusuf (PT. LARPA JAYA PUBLISHER, 2025)
The practice of Ramadan fasting, as intermittent fasting, is growing in popularity because of its ability to prevent cancer development. The practice of fasting allows patients to experience multiple changes at metabolic, physiological, and epigenetic levels, which reduce cancer advancement and better their response to treatment. The study performs a systematic review of published studies to explore protective mechanisms within this investigation about assurance of scientific integrity and transparency. The authors have implemented the standards included in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The research demonstrates how fasting metabolism affects ketone body production while reducing glucose availability and simultaneously lowering both insulin and insulin-like growth factor-1 (IGF-1) levels. Proliferation control of cancer cells depends heavily on these three regulatory factors. The DNA damage response (DSR) becomes more effective while cellular homeostasis maintains itself because fasting-induced autophagy accomplishes both cellular component elimination and defective cellular component clearance. The reduction of oxidative stress caused by fasting leads to constrained development of malignant cell transformations and protects against DNA. The epigenetic effects of fasting during Ramadan result in non-coding RNA regulation, together with DNA methylation and histone remodeling processes to turn on beneficial tumor suppressor genes and deactivate cancer-causing oncogenes. The latest research supports the potential role of fasting as an additional form of care for fighting and stopping cancer development. These findings lead to major impacts on clinical applications and dietary remedies, and public health policy within integrative cancer treatment.